2017
DOI: 10.3233/jad-170086
|View full text |Cite
|
Sign up to set email alerts
|

Memory is Not Enough: The Neurobiological Substrates of Dynamic Cognitive Reserve

Abstract: Changes in the residual memory variance are considered as a dynamic aspect of cognitive reserve (d-CR). We aimed to investigate for the first time the neural substrate associated with changes in the residual memory variance overtime in patients with amnestic mild cognitive impairment (aMCI). Thirty-four aMCI patients followed-up for 36 months and 48 healthy elderly individuals (HE) were recruited. All participants underwent 3T MRI, collecting T1-weighted images for voxel-based morphometry (VBM). They underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…Reed and co-workers [13] proposed the concept of dynamic CR, measured in terms of changes in memory functions. Zahodne and colleagues [14,15] and Serra and co-workers [16] extended the concept of dynamic CR. These studies quantified CR as residual variance of memory scores, after accounting for demographical and brain damage variables.…”
Section: Static and Dynamic Reserve's Indexesmentioning
confidence: 99%
See 4 more Smart Citations
“…Reed and co-workers [13] proposed the concept of dynamic CR, measured in terms of changes in memory functions. Zahodne and colleagues [14,15] and Serra and co-workers [16] extended the concept of dynamic CR. These studies quantified CR as residual variance of memory scores, after accounting for demographical and brain damage variables.…”
Section: Static and Dynamic Reserve's Indexesmentioning
confidence: 99%
“…To conceptualize CR in terms of residual variance of memory functions made the CR's concept more flexible and adaptable to cognitive changes. However, Serra and co-workers [16] have recently shown that indices of dynamic CR that strip off any contribution of general cognitive abilities to retain exclusively memory processes are not able to identify the conversion to AD efficiently. The integrity of memory function is not sufficient to withstand neurodegeneration [16].…”
Section: Static and Dynamic Reserve's Indexesmentioning
confidence: 99%
See 3 more Smart Citations